Odpowiedź :
Odpowiedź:
A)6x+12=42
6x= 42-12
6x= 30 |:6
x=5
Lewa strona:x
Prawa strona: 5
B) 40-6x=28
40-28=6x
12=6x |:6
2= x
L: 2
P: x
c) 3x-12=2x+1
L:x
P:13
d) 4x-3=7x-24
24-3=7x-4x
21=3x |:3
7= x
L: 7
P:x
e) 3x+7= -5
3x= -5-7
3x= -12 |:3
x= -4
L: x
P:-4
f) -8x+4=5x+16
4-16= 5x+8x
-12= 13x |:13
-12/13=x
L: -12/13
P: x
g) 2(x+6)= -4
2x+12=-4
2x= -12-4
2x= -16 |:2
x= -8
L:x
P: -8
Zadanie 2
a)2a-3=a+1
2a-a= 1+3
a=4
b) 4b+3=3b-4
4b-3b= -4-3
b= -7
c) 7+3c=5+2c
3c-2c= 5-7
c= -2
d) 5d+2=3d
5d-3d=-2
2d= -2 |:2
d= -1
e) 6f-1=f+2
6f-f= 2+1
5f= 3 |:5
f= ⅗